FRI0615 Sarcoidosis and cancer: different patterns of association in a multicenter cohort from southern europe. (15th June 2017) - Pérez-Alvarez, R; Kostov, B; González, A García; Torre, R Gόmez De La; Dupla, M Lopez; Escalante, B De; Alguacil, A; Chara, J; Velilla, J; Rascόn, J; Morillo, JS Garcia; Tolosa, C; et al.
Abstract : Objectives: To evaluate the temporal association between the diagnosis of neoplasia and sarcoidosis in a large cohort of Spanish patients with sarcoidosis. Methods: In January 2016, the Autoimmune Diseases Study Group (GEAS-SEMI) created a national registry (SARCOGEAS) of patients with sarcoidosis. Sarcoidosis was diagnosed with the criteria proposed by the ATS/ERS/WASOG 1999 statement, and extrathoracic disease by the 2014 WASOG instrument. Diagnosis of neoplasia was recorded before and after the diagnosis of sarcoidosis. Results: The cohort included 1082 patients (82% biopsy-proven, 618 women, mean age 47yrs). Association with neoplasia was detected in 135 (13%) patients who developed 140 neoplasms (110 solid and 30 hematological neoplasia). The neoplasia more frequently reported were breast (n=18), lymphoma (n=16), non-melanoma skin (n=15) and colon (n=15). Association with neoplasia was more frequent in patients born in Spain (97% vs 86%, p<0.001, OR 4.06), older patients (55 vs 46yrs, p<0.001, OR 1.03) and those with bone marrow involvement (14% vs 4%, p<0.001, OR 3.64). Patients in whom cancer preceded the diagnosis of sarcoidosis had a higher frequency of sarcoidosis diagnosed incidentally (20% vs 4%, p=0.011) and a lower frequency of ocular sarcoidosis (3% vs 16%, p=0.016). Patients with associated hematological neoplasia had a higher frequency of ENT (13% vs 1%, p=0.009) and bone marrow (33% vs 9%, p=0.002) involvements in comparison with patients with associated solid neoplasia. Conclusions: Association between sarcoidosis and cancer was found in 13% of patients (80% solid and 20% hematologic malignancies). Elderly patients and those born in Spain were at high risk of having associated cancer. Asymptomatic sarcoidosis was more frequently observed in those patients with a previous history of neoplasia, while the association with hematological neoplasms was linked to a higher frequency of sarcoidosis involving ENT and bone marrow. Disclosure of Interest: None declared